United States-based practice guidelines for children and adolescents with eating disorders - Cara Bohon; Daniel Le Grange; Evelyn Attia; Neville H. Golden; Dori Steinberg (Journal of Eating Disorders)
Abstract Introduction Several practice guidelines exist from professional organizations in the United States to support the assessment and management of eating disorders in children and adolescents. This manuscript synthesizes the key areas of overlap from these guidelines and provides directions for future research and alignment to improve care. Recommendations Consistent screening for eating disorders in primary care is recommended to ensure early identification and referral to treatment. Outpatient treatment supported by families, including family based treatment, is the first line of care recommended by guidelines. Multidisciplinary treatment teams benefit patients in covering the variety of aspects of health that eating disorders impact, including mental health, nutritional health, and physical health. Patients may require hospitalization under certain medical criteria such as bradycardia or specific lab abnormalities. Conclusions Guidelines show consensus on the importance of early identification and treatment access, involvement of family in treatment, and the use of a multidisciplinary treatment team. However, future work is needed to guide care of Avoidant/Restrictive Food Intake Disorder (ARFID), as well as the impact of weight inclusive care and the development of validated screening tools for children and adolescents for all eating disorders.